Influence of storm electromagnetic field on the aircraft crew - Азнакаев, Э. Г.; Протоерейский, А. С. (Proceedings of National Aviation University (archive), 2000)
Considered is the biophysical influence of alternative electromagnetic fields, caused by electrical discharges in atmosphere. Analyzed are conditions which may provoke inadequate actions and errors of the crew in airplane flight control